Efektivitas Perangkat Pembelajaran Biologi Berbasis Lab Mini Melalui Pembelajaran Kooperatif - Fatikhatun Nikmatus Sholihah (JoEMS (Journal of Education and Management Studies), 2019)
ABSTRACT This study aims to know effectiveness of learning packaging oriented on mini laboratory implemented uses Cooperative Learning at Senior Hight School Ngoro Jombang. This research used trial design one group pretest-posttest design with quantitative and qualitative descriptive analysis techniques. Based on the result of data analysis, obtained some following result: a) student learning result is 80,6% complete in cognitive competence and 100% in psicomotor, very good in afective competences, b) the students have positive respons in their interest of learning process, c) the quality level of lesson plan done is high and obstacles that occur in teaching are the number of group members is too large. Based on the result of data analysis, it can be concluded that learning packaging oriented on mini laboratory implemented uses cooperative learning is effective on the topic of Fungi, but adjustable with the situaton and condition of the school, specifically equipments of the laboratory. Keywords: Mini Lab; Learning Cooperatif; Student Learning Result. ABSTRAK Penelitian ini bertujuan untuk mengetahui efektivitas perangkat pembelajaran berorientasi Lab Mini yang diimplementasikan melalui pembelajaran kooperatif di SMA Ngoro Jombang. Penelitian ini menggunakan desain uji coba penelitian menggunakan one group pretest –posttest design dengan teknik analisis deskriptif kuantitatif dan deskriptif kualitatif. Berdasarkan hasil analisis data diperoleh beberapa hal sebagai berikut: a) hasil belajar siswa 80,6% tuntas untuk kompetensi kognitif, 100% untuk kompetensi psikomotor serta sangat baik untuk kompetensi afektif, b) siswa memberikan respon positif terhadap ketertarikannya pada proses pembelajaran, c) hambatan ketika proses pembelajaran berlangsung adalah jumlah anggota kelompok terlalu banyak. Berdasarkan hasil analisis dapat disimpulkan bahwa perangkat pembelajaran berorientasi Lab Mini yang diimplementasikan melalui pembelajaran kooperatif efektif pada materi Fungi, tetapi disesuaikan dengan situasi dan kondisi sekolah khususnya pada tersedianya alat-alat laboratorium. . Kata Kunci: Mini Lab; Pembelajaran Kooperatif; Hasil Belajar Siswa